A case study of public real estate management in chosen countries - Gross, Marta; Źróbek, Ryszard (International Conference “Environmental Engineering”, 2017)
Real estate management is a system. It consists of relations, procedures and processes occurring between entities and subjects at real estate market. It is helpful in proper decision-making based on information about the entities (and their needs) and the state of a property. Real estate management is different in various countries. The case study research was carried out on three chosen public real estate management systems: German, Polish and Swiss. The paper presents some basic information about public real estate management in analysed countries. The authors conducted an analysis of the systems using some indicators and geospatial analysis which was performed with use of GIS tools. It gives the opportunity to estimate and show differences and similarities between analysed systems. The paper shows that there is a possibility to use some international indicators to compare public real estate management systems. So there is still a need to improve these systems more and more.
Keywords: management; public real estate; case study